Speech and language development with the background application of dialects (Training and Practice : Journal of Educational Sciences, 2020)
The language of students entering third level education institutes is continuously influenced by the media, the spoken everyday language and terminologies which can have negative and positive effects on their language and as a result a kind of pidginization of the Hungarian language can occur. Consequently, it is crucial for students taking part in the nursing and tutoring education to get acquainted with the rich phonological, lexical, syntactical and structural phenomena of the various Hungarian dialects. The various methods of anthropological linguistics can also be helpful in their studies. The observation, description and understanding of elements of the dialect supports not just the understanding of text in relation to pre-school teacher training but it also helps to accept one’s own native tongue ordialect. The determinant source of native language education is the traditional Hungarian language and its linguistic specialities. The first sounds a child perceives are the voices of their environment – the sounds of articulation and intonation in a dialectal background. These special idiomatic and vernacular features appear in the nursery rhymes and folk tales as well. These features help pre-school children to improve their mother language skills.